A woman's place: US counterterrorism since 9/11 - Cook, Joana (Oxford University Press, 2020)
"The 9/11 attacks fundamentally transformed how the US approached terrorism, and led to the unprecedented expansion of counterterrorism strategies, policies, and practices. While the analysis of these developments is rich and vast, there remains a significant void. The diverse actors contributing to counterterrorism increasingly consider, engage and impact women as agents, partners, and targets of their work. Yet, flawed assumptions and stereotypes remain prevalent, and it remains undocumented and unclear how and why counterterrorism efforts have evolved as they did, including in relation to women. Drawing on extensive primary source documents, A Woman's Place traces the evolution of women in US counterterrorism efforts through the administrations of Presidents Bush, Obama, and Trump, examining key agencies like the US Department of Defense, the Department of State, and USAID. In their own words, Joana Cook investigates how and why women have developed the roles they have, and interrogates US counterterrorism practices in key countries like Iraq, Afghanistan, and Yemen. Analysing conceptions of and responses to terrorists, she also considers how the roles of women in Al- Qaeda and Daesh have evolved and impacted on US counterterrorism considerations."--